The Role of Intestinal Mucosal Barrier in Autoimmune Disease: A Potential Target - An, Jia; Liu, Yuqing; Wang, Yiqi; Fan, Ru; Hu, Xiaorong; Zhang, Fen; Yang, Jinhua; Chen, Junwei (Frontiers in Immunology, 2022)
Autoimmune diseases are a series of diseases involving multiple tissues and organs, characterized by the over production of abnormal multiple antibodies. Although most studies support that the impaired immune balance participates in the development of autoimmune diseases, the specific pathogenesis of it is not fully understood. Intestinal immunity, especially the intestinal mucosal barrier has become a research hotspot, which is considered to be an upstream mechanism leading to the impaired immune balance. As an important defense barrier, the intestinal mucosal barrier regulates and maintains the homeostasis of internal environment. Once the intestinal barrier function is impaired under the effect of multiple factors, it will destroy the immune homeostasis, trigger inflammatory response, and participate in the development of autoimmune diseases in the final. However, the mechanism of the intestinal mucosal barrier how to regulate the homeostasis and inflammation is not clear. Some studies suggest that it maintains the balance of immune homeostasis through the zonulin pathway, intestinal microbiome, and Toll-like receptor signaling pathway. Our review focused on the composition and the function of the intestinal mucosal barrier to describe the research progress of it in regulating the immune homeostasis and inflammation, and also pointed that the intestinal mucosal barrier was the potential targets in the treatment of autoimmune diseases.